Analisis Risiko Finansial Dan Operasional Pada Usaha Mabel Skala Mikro Dan Kecil Di Desa Debong Wetan - Maulana, Ryan Mughni; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Micro- and small-scale furniture businesses play a vital role in the rural economy, yet their operations are still faced with various risks that can disrupt business sustainability. This study aims to analyze the financial and operational risks faced by micro- and small-scale furniture businesses in Debong Wetan Village and formulate appropriate risk management strategies. The study employed a qualitative approach with descriptive methods, collecting questionnaire data from furniture business owners and managers. The analysis involved risk identification, risk measurement using a combination of likelihood and impact levels, risk mapping in a risk map, and determining risk management strategies. The results indicate that the main risks faced include fluctuations in raw material prices, workplace accidents, and damage to production equipment and machinery, all of which are classified as high-risk. Furthermore, the risks of raw material delays, declining market demand, and business competition are categorized as medium-risk, while legal risks and recording of past risks are categorized as low-risk. Risk management is carried out through preventive and corrective approaches tailored to each risk level. Overall, this study concludes that furniture businesses have a sufficient risk management foundation, but operational risk mitigation efforts are still needed to enhance long-term business resilience and sustainability.